2003
DOI: 10.1254/jphs.91.219
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of Enterohemorrhagic Escherichia coli O157:H7 Infection to Assess Immunopotentiating Activity of Drugs on Mucosal Immunity: Effect of Drugs

Abstract: An enterohemorrhagic Escherichia coli (EHEC) O157 oral infection murine model was established to examine the potentiating activity of drugs on mucosal immune responses. Groups of ICR mice inoculated intragastrically with 10(11) CFU/kg EHEC O157 showed chronic intestinal infection with the pathogen that persisted over 3 weeks and resulted in the synthesis of relatively high levels of antigen specific fecal IgA antibody. Intraperitoneal administration of 80 NU/kg Neurotropin, an immunopotentiator, augmented the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Serum IgA levels were higher on day 7 than on day 1 in all infected groups, indicating a delayed response even though the mice were back to their pre-infection body weights and no longer showed any symptoms of the infection. Nagano et al (2003) demonstrated that fecal IgA antibody titres against EHEC O157 whole cells and O157-LPS peaked at 4-weeks after inoculation with 10 11 cfu kg À1 , which suggests that the increased secretion of IgA continues for weeks after the infection.…”
Section: Effect Of the Whey Protein Isolate And Peptide Fractions In mentioning
confidence: 92%
“…Serum IgA levels were higher on day 7 than on day 1 in all infected groups, indicating a delayed response even though the mice were back to their pre-infection body weights and no longer showed any symptoms of the infection. Nagano et al (2003) demonstrated that fecal IgA antibody titres against EHEC O157 whole cells and O157-LPS peaked at 4-weeks after inoculation with 10 11 cfu kg À1 , which suggests that the increased secretion of IgA continues for weeks after the infection.…”
Section: Effect Of the Whey Protein Isolate And Peptide Fractions In mentioning
confidence: 92%
“…ous paper. 18) On the other hand, GPU991 and GPU992 disappeared from the feces within 2 weeks and did not induce the fecal IgA antibody production. Then, GPU991 as well as heatkilled GPU96MM and IID5208 (nonpathogenic E. coli) were repeatedly inoculated 4 times into mice to increase the antigen loading.…”
Section: Discussionmentioning
confidence: 94%
“…Again, GPU991 (espA-deletion mutant), GPU992 (sepLdeletion mutant) and A6-E7 (sepL-insetion mutant) could not form the TTSS, and showed no adherence to cultured epithelial cells. 10,18) On the other hand, G1-E11 (tir-insertion mutant) and Δeae (eae-deletion mutant) adhered diffusely to Caco-2 cells through the TTSS but not establish intimate adhesion through intimin-Tir interaction. 10) Considering all together, the results strongly suggest that the adhesion of EHEC through the intimin-Tir interaction is essential for the induction of antigen-specific S-IgA antibody production in the intestine of mice.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Stx-1 and Stx-2 concentrations were determined by ELISA [61] using mouse anti-Stx-1B subunit monoclonal antibody (STX1-13C4; Toxin Technology, Sarasota, FL, USA) or anti-Stx-2B subunit monoclonal antibody (STX2-BB12; Toxin Technology) as a capture antibody, and mouse anti Stx-1 and Stx-2 pooled antibodies conjugated to horseradish peroxidase (STXPC-1; Toxin Technology) as a developing antibody. Purified Stx-1 and Stx-2 purchased from Nacalai Tesque, Inc. (Kyoto, Japan) were used to prepare the standard curves.…”
Section: Methodsmentioning
confidence: 99%